R&D on control of vibrations under covicocepad during 2007-2008 - Barros, Rui (2012)
This paper provides information on the latest R&D within COVICOCEPAD project approved in the framework of Eurocores program. It addresses the use of TLD, base isolation devices, MR dampers and a hybrid technique using both devices together. Some results are provided associated with calibration of a MR damper at FEUP, as well as its inclusion in a small scale laboratory set-up with proper equations of motion of the controlled smart structure. An application of semi-active control technique to a bridge is outlined. Further remarks and details on future tests to be performed in LNEC shaking table, within COVICOCEPAD project, are provided.